Mutations in the non-coding RNU4ATAC gene affect the homeostasis and function of the Integrator complex. Issue 2 (20th December 2022) - Almentina Ramos Shidi, Fatimat; Cologne, Audric; Delous, Marion; Besson, Alicia; Putoux, Audrey; Leutenegger, Anne-Louise; Lacroix, Vincent; Edery, Patrick; Mazoyer, Sylvie; Bordonné, Rémy
Abstract: Various genetic diseases associated with microcephaly and developmental defects are due to pathogenic variants in the U4atac small nuclear RNA (snRNA), a component of the minor spliceosome essential for the removal of U12-type introns from eukaryotic mRNAs. While it has been shown that a few RNU4ATAC mutations result in impaired binding of essential protein components, the molecular defects of the vast majority of variants are still unknown. Here, we used lymphoblastoid cells derived from RNU4ATAC compound heterozygous (g.108_126del;g.111G>A) twin patients with MOPD1 phenotypes to analyze the molecular consequences of the mutations on small nuclear ribonucleoproteins (snRNPs) formation and on splicing. We found that the U4atac108_126del mutant is unstable and that the U4atac111G>A mutant as well as the minor di- and tri-snRNPs are present at reduced levels. Our results also reveal the existence of 3'-extended snRNA transcripts in patients' cells. Moreover, we show that the mutant cells have alterations in splicing of INTS7 and INTS10 minor introns, contain lower levels of the INTS7 and INTS10 proteins and display changes in the assembly of Integrator subunits. Altogether, our results show that compound heterozygous g.108_126del;g.111G>A mutations induce splicing defects and affect the homeostasis and function of the Integrator complex.